(untitled) (Indian Journal of Public Health Research & Development, 2020)
Introduction and Hypothesis: Pelvic Organ Prolapse (POP) is a condition with specific signs such as descent of the fornix anterior, fornix posterior, uterine, cervix, apex of the vagina after hysterectomy or perineal. The use of pessary is a conservative and the first line of POP medication. Most women who used pessaries complained about vaginal discharge, more than 50% of them were proven suffered from bacterial vaginosis. This research was aimed to know whether there was any association between the incident of BV with the use of pessaries and the length use of pessaries among POP patients. We hypothesized that the use of pessaries and the length use of pessaries had a significant association with the incident of BV. This study was a case-control study. There were 68 medical records, which were obtained through purposive sampling. Independent variables were the use of pessaries and the length use of pessaries, the dependent variable was the incident of BV among POP patients. Data collection sheets were the instrument of this research. Chi Square, Fisher Exact Test and Odd ratio were used to analyze the data. This research used ?: 5%, CI: 95% Result: This research revealed that there was a significant association between the incident of BV on POP patients with the using of pessaries (P=0.001) and the length use of pessaries (P=0.024). Odd ratio 5.9 (95% CI, 1.95-17.97) means patients with POP who used pessaries had a probability to suffer BV 5.9 times higher than those who didn’t. Conclusion: there was a significant association between the incident of BV with the use of pessaries and the length use of pessaries on POP patients.